Aprendizagem máxima e participação guiada: caminhos para a valorização da participação educativa da comunidade - Pando, Ana Carolina (Universidade Federal de São Carlos, 2025)
This undergraduate thesis focused on the concept of guided participation by Barbara Rogoff from the perspective of dialogic learning, articulating arguments aimed at contributing to the exercise of citizenship and the promotion of human rights for all individuals within the school environment, thereby involving the need to concretize learning. However, Brazil faces numerous challenges in implementing educational actions that can lead all students to academic success, hindering the maximum learning potential of students. As a condition for achieving this fundamental ability in school education, it is necessary to shift the focus of learning, that is, to move away from a unidirectional monologue from the teacher to the students, and instead involve the entire community that constitutes the children's environment, based on dialogue as a claim to validity in relationships. In this context, community participation in schools within multicultural settings is crucial, especially for social minorities, as it connects classroom activities with those of the family and community contexts. With the aim of contributing to this purpose, this monograph addressed the following question: what are the contributions of Barbara Rogoff's concept of guided participation to grounding maximum learning in Brazilian schools through the educational participation of the community? This question was developed based on the general objective of relating the concept of maximum learning to that of guided participation, identifying elements that support the relationship between family, school, and community to enhance academic success and strengthen the educational participation of the community. Beyond being an institutional space, the concepts demonstrate that schools, to fulfill their social function, need to be integrated with the local community, thereby assigning possibility and potential for action to the realization of human rights and social equity. By offering resources for pedagogical training and research aimed at the sustainability of Successful Educational Actions and the educational participation of the community in the Brazilian context, it is hoped that this work will contribute to valuing the active presence of communities in schools, embracing them with high expectations, affection, and science, and bringing communicative scientific data closer to the reality of schools.
Maximum learning and guided participation: paths to enhance the educational participation of the community
Máximo aprendizaje y participación guiada: caminos para potenciar la participación educativa de la comunidad
Keywords: Aprendizagem; Relação família, escola e comunidade; Cidadania; Participação social; Psicologia sociocultural; Learning; Family, school, and community relationship; Citizenship; Social participation; Sociocultural psychology; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM